2011
DOI: 10.2478/v10172-011-0050-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Bonding Zone of Explosively Welded Sheets

Abstract: In the presented paper two sets of Al/Cu and Ti/Ni sheets bonded through the explosive welding process was thoroughly analyzed. A particular attention was drawn to describe the changes in microstructure and chemical composition within the volumes close to the bonding interface. Optical microscopy as well as scanning (SEM) and transmission (TEM) electron microscopy were applied in the above studies whereas strain hardening across the welding zone was determined by Vickers microhardness measurements.Optical micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 9 publications
3
17
1
Order By: Relevance
“…The microstructure of SS plate in layers adjacent to the Cu sheet is composed of fine (sub)grains with a diameter of a few hundreds of nanometers (mostly <500 nm). A large number of dislocations accommodated in the cells/(sub)grains of both metals is a strong indication that the deformation processes are prevailing over the thermally activated softening ones, i.e., recovery and recrystallization, as suggested earlier for Al/Cu [9], Zr/(carbon steel) [10] and Al/Ti [14] clads. The wave valleys do not contain any macroscopically visible solidified melt zones (Figure 7a-c).…”
Section: Dislocation Structure Of Parent Sheets-tem Analysissupporting
confidence: 55%
See 1 more Smart Citation
“…The microstructure of SS plate in layers adjacent to the Cu sheet is composed of fine (sub)grains with a diameter of a few hundreds of nanometers (mostly <500 nm). A large number of dislocations accommodated in the cells/(sub)grains of both metals is a strong indication that the deformation processes are prevailing over the thermally activated softening ones, i.e., recovery and recrystallization, as suggested earlier for Al/Cu [9], Zr/(carbon steel) [10] and Al/Ti [14] clads. The wave valleys do not contain any macroscopically visible solidified melt zones (Figure 7a-c).…”
Section: Dislocation Structure Of Parent Sheets-tem Analysissupporting
confidence: 55%
“…This leads to the formation of wavy interfaces between the joined sheets. Since the interfacial layers are subjected to severe plastic deformation [14][15][16][17][18] they can easily undergo recovery and recrystallization. On the other hand, the processes of fast heating followed by fast cooling during clad preparation result in the formation of solidified melt zones of different structures, phase composition and mechanical properties [7][8][9][10][11]19,20].…”
Section: Macro-/meso-scale Interfaces Overviewmentioning
confidence: 99%
“…[22][23][24][25][26][27] It was found that wavy interfaces with a limited quantity of melt zones produce better mechanical properties in contrast to flat melt bonds. [20] However, too much waviness [28,29] and too many melt zones which form a semi-continuous interlayer can exert a detrimental effect on the performance of the bimetal.…”
Section: Introductionmentioning
confidence: 99%
“…The other reasons of ratcheting phenomenon in the analyzed bimetal that could be consider are specific structural and mechanical properties of joint area. During the collision of flayer plate with base plate very high pressure around 19-50 GPa is created in time around 2-5  (Walczak, 1989;Crossland, 1982) as a result thin very hard layer of intermetallics is formed (Paul et al, 2011) sometimes with larger local melted areas. Those melted areas could already have very short cracks (Fig.…”
Section: Simmulationsmentioning
confidence: 99%